Cord blood chemerin: differential effects of gestational diabetes mellitus and maternal obesity. (5th April 2013) - van, Mireille N. M.; Zeck, Willibald; Ulrich, Daniela; Schest, Eva‐Christina; Hirschmugl, Birgit; Lang, Uwe; Wadsack, Christian; Desoye, Gernot
Summary Objective Chemerin is a novel adipokine implicated in inflammation and obesity. We hypothesized that foetal chemerin would be elevated in gestational diabetes mellitus (GDM) and correlate with foetal and maternal adiposity. Design Observational, longitudinal study. Subjects and measurements Foetal chemerin was measured separately in arterial and venous cord blood of 30 infants born to mothers with (n = 15) and without GDM (n = 15), in their mothers in early third trimester and at delivery and in amniotic fluid (week 32) of women with GDM. Expression of chemerin and its receptor in human foetal tissues commercially available and in placental cells was measured by quantitative PCR. Associations between foetal and maternal anthropometric and metabolic variables were assessed in multivariate regression models. Results In GDM, foetal arterial but not venous cord blood chemerin levels were elevated by about 60% (P < 0·05). Venous cord blood chemerin was higher in infants of obese women (P < 0·01). In multivariate analyses, neither amniotic fluid nor cord blood chemerin levels correlated with birth weight or ponderal index. Both arterial and venous chemerin levels were related to maternal chemerin at birth, and arterial chemerin was associated with GDM status in addition. Maternal levels were unaltered in GDM, but higher in maternal obesity. Foetal liver produces fourfold more chemerin mRNA than other foetal tissues, whereas its receptor prevails in spleen. Conclusions Based on multivariate analyses, foetal growth appears unrelated to foetal chemerin. Maternal obesity and GDM have differential effects on foetal chemerin levels. Site of major production (liver) and action (spleen) differ in human foetal tissues.